Assessment of anticancer properties of cumin seed (Cuminum cyminum) against bone cancer - Chandrasekaran, Rajkuberan; Krishnan, Muthukumar; Chacko, Sonu; Gawade, Omkar; Hasan, Sheik; Joseph, John; George, Evelin; Ali, Nemat; AlAsmari, Abdullah F.; Patil, Sandip; Jiang, Haoli (Frontiers in Oncology, 2023)
Early-life osteosarcoma is associated with severe morbidity and mortality, particularly affecting young children and adults. The present cancer treatment regimen is exceedingly costly, and medications like ifosfamide, doxorubicin, and cisplatin have unneeded negative effects on the body.With the introduction of hyphenated technology to create medications based on plant molecules, the application of ayurvedic medicine as a new dimension (formulation, active ingredients, nanoparticles) in the modern period is rapidly growing. The primary source of lead compounds for the development of medications for a variety of ailments was plants and their products.. Traditionally, Cuminum cyminum (cumin) has been used as medication to treat a variety of illnesses and conditions. In the current investigation, we used solvents to extract the cumin seed residue and evaluated its potential therapeutic benefits in MG 63 cells. First, we used the MTT assay to test the extracted residue's cytotoxicity. The results show that hexane extract (IC50 86 µG/mL) efficiently inhibits cells by causing programmed cell death. Furthermore, using the AO/EB staining method, the Lactate Dehydrogenase Assay (LDH), and the Reactive Oxygen Species (ROS) assay using the DCHFDA staining method, we have demonstrated that the hexane extract causes apoptosis in MG 63 2 This is a provisional file, not the final typeset article cells. Furthermore, flow cytometry research revealed that the hexane extract stops the cell cycle in the S phase. Additionally, the hexane extract limits colony formation and the migration potential as shown by the scratch wound healing assay. Furthermore, the extract from cumin seeds exhibits remarkable bactericidal properties against infections that are resistant to drugs. Gas chromatography analysis was used to quantitatively determine the hexane and methanolic extract based on the experimental data. The primary chemical components of the extract are revealed by the study, and these help the malignant cells heal. The present study finds that there is scientific validity in using cumin seeds as a novel method of anticancer therapy after undergoing both intrinsic and extrinsic research.